Partisipasi Masyarakat dalam Pengembangan Desa Wisata Tampaksiring di Kabupaten Gianyar, Bali - Parmita, I Ketut Agus Giri; Pujaastawa, Ida Bagus Gde; Suwena, I Wayan (Sunari Penjor : Journal of Anthropology, 2022)
A tourism village is one kind of tourism that offers tourism potential owned by a village. Tampaksiring Village is one of the villages that had becoming a tourism village in Gianyar Regency, Bali. One of the concepts in the development of tourist villages is community-based development which focuses on local community participation. Thus, it is to be expected that the benefits of tourism will be more for the local community as the legal owner of the resources. This study aims to 1) identify and explain the profile of tourism potential in Tampaksiring Tourism Village, 2) explain the community participation in the development of Tampaksiring Tourism Village, 3) explain the implications of the development of Tampaksiring Tourism Village. This study uses a qualitative method. Data collection is done through observation, interviews, literature studies, and document studies both online or offline. The theory used to analyze the problem in this study is the theory of participation and the theory of tourism impact. The results of this study indicate that the Tampaksiring Tourism Village has a variety of tourism potentials that can be developed as a tourist attraction. Local communities have a role in the planning, implementation, management, and evaluation processes in the development of tourism villages. Tourism activities in the Tampaksiring Tourism Village also have both positive and negative impacts on economic, socio-cultural, and environmental aspects.